Maurice Carême, Bruges : La ville dans le miroir de la poésie et de la photographie - Tóth, Ágnes (Verbum – Analecta Neolatina, 2013)
Bruges by Maurice Carême is a work in collaboration with the Italian photographer, Fulvio Roiter, and contains 60 poems by Carême and 65 photos by Roiter. Since its first publication in 1963, the book has seen three editions. It aims to be a photoraphic image of the city of Bruges, it provides a visible and readable reflection of it — it can be “seen” and “read” at the same time. In this paper, I intend to show the iconicity of writing, the photographic image in poetry, the relationship of text and image, and the rhythms in the relationship between text and photos. The photoes can be watched and read, and thus the books brings our eyes to the images from the writing and to the writing from the images, from the great plane to details and vice versa. It helps to integrate into a whole the proximity, the intimacy, the interiority and the distance.